2000
DOI: 10.1090/s0002-9939-00-05724-5
|View full text |Cite
|
Sign up to set email alerts
|

An order characterization of commutativity for 𝐶*-algebras

Abstract: Abstract. In this paper, we investigate the problem of when a C * -algebra is commutative through operator-monotonic increasing functions. The principal result is that the function e t , t ∈ [0, ∞), is operator-monotonic increasing on a C * -algebra A if and only if A is commutative. Therefore, C * -algebra A is commutative if and only if e x+y = e x e y in A+C for all positive elements x, y in A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…[2,3]). Very recently, Wu in [6] gave another characterization for commutativity based on the function exp x. We observe that both x p and exp x are monotone increasing functions on the positive axis but not operator monotone on M 2 , the matrix algebra of all complex 2 × 2 matrices.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…[2,3]). Very recently, Wu in [6] gave another characterization for commutativity based on the function exp x. We observe that both x p and exp x are monotone increasing functions on the positive axis but not operator monotone on M 2 , the matrix algebra of all complex 2 × 2 matrices.…”
mentioning
confidence: 83%
“…If we make use of the operator monotone property of the log function, we can deduce from monotone assumption for exp the monotone property of the function x t for any t > 1. To discuss on a C * -algebra, this will also considerably shorten the proof in [6], where Wu reduces his whole proof to the monotone property of the function x 2 and uses the old Ogasawara's result [2]. On the matrix algebra M 2 however, we prefer the above elementary approach.…”
mentioning
confidence: 99%
“…We recall that in the literature one can find several conditions characterizing commutativity of * -algebras most of which are related to the order structure; see, for example, [4][5][6][7][8]. A characterization of algebraic character can be found in [9].…”
mentioning
confidence: 99%
“…A few comments on this modified conjecture follow. First, we refer to the paper [10] where it was shown that if the exponential function on the interval [0, ∞[ is monotone increasing relative to a given * -algebra A (meaning that for any , ∈ A with 0 ≤ ≤ we have exp( ) ≤ exp( )), then the algebra A is commutative. In [11]…”
Section: Clearly the Order Inmentioning
confidence: 99%